Extracorporeal membrane oxygenation in an HIV-positive man with severe acute respiratory distress syndrome secondary to pneumocystis and cytomegalovirus pneumonia. (February 2018) - Morley, Deirdre; Lynam, Almida; Carton, Edmund; Martin-Loeches, Ignacio; Sheehan, Gerard; Lynn, Niamh; O'Brien, Serena; Mulcahy, Fiona
The management of critically ill human immunodeficiency virus (HIV)-positive patients is challenging; however, intensive care unit-related mortality has declined significantly in recent years. There are 10 case reports in the literature of extracorporeal membrane oxygenation (ECMO) use in HIV-positive patients, of whom seven survived to hospital discharge. We describe a 33-year-old Brazilian man who presented with Pneumocystis jirovecii pneumonia and severe hypoxic respiratory failure. He developed refractory acute respiratory distress syndrome (ARDS) and was commenced on veno-venous ECMO. He was successfully decannulated following 21 days of ECMO and survived to hospital discharge. Despite poor evidence surrounding the use of ECMO in immunocompromised patients, it is evident that ECMO could represent an important rescue therapy in HIV-positive patients with refractory ARDS.